Management of Training Process of Team Sports Athletes During the Competition Period on the Basis of Programming (Football-Based) - Shchepotina, Natalia; Kostiukevych, Viktor; Asauliuk, Inna; Stasiuk, Vadym; Vozniuk, Tetiana; Dmytrenko, Svitlana; Adamchuk, Vadym (Physical Education Theory and Methodology, 2021)
The purpose of the study was to experimentally substantiate the effectiveness of organization of structural arrangements of the training process in skilled football players within the limits of the competition period on the basis of programming. Material and methodology. 18 skilled football players of “Burevisnyk” student team took part in the research. The average age of participants was 19.8 ± 5.8 years and the qualification was category 1. The programme of the competition period of the skilled football players consisted of four blocks: the first one included the types and ratios of the training work, the second one included quantitative indexes of training sessions (non-specific, specific, comprehensive) and games (educational, control, official), and the third one included the ratio of means (general preparatory exercises, special preparatory exercises, developing exercises, competitive exercises) and training loads (aerobic, mixed aerobic and anaerobic, anaerobic alactic, anaerobic glycolytic loads), and the fourth one included preparedness criteria. Results. We have redistributed training loads of various orientation by taking into account the specifics of competitive loads in skilled football players. Thus, shares of loads of the aerobic and anaerobic glycolytic orientation at the formative stage of the experiment were increased by 53.6 and 3.0 %, respectively, and the loads of the mixed and anaerobic alactic orientation were decreased by 40.0 and 3.4 %, respectively. Positive dynamics of indexes of physical (1.2-2.2 %) and functional (5.4-6.7 %) preparedness and competitive activity (3.6-23.8 %) of skilled football players at the formative phase of the experiment in comparison to the ascertaining phase was evident. Conclusions. Theoretical and methodical aspects of programming of the training process may be conditioned upon the hierarchical structure, in which smaller programmatic structural arrangements are subordinate to the larger ones; the objectives with respect to the training programmes at every phase of the training macrocycle; general and special principles of athlete training; algorithmicity, i.e. step-by-step planning and correction of managerial influences; proper selection of training means and use of training loads with different focuses in the process of training cycles; use of informational criteria for control at every phase of the training process.